Penyuluhan Personal Hygiene dan Pemeriksaan Kesehatan pada Pembudidaya Rumput Laut di Lingkungan Pattitangngang Kabupaten Takalar - Syafitri, Nurul Mawaddah; M. Anas (Education and Talent Development Center Indonesia, 2024)
The concept of personal hygiene in everyday life is very important and must be applied properly, because someone who applies the concept of personal hygiene properly and correctly will greatly affect their own health conditions. The purpose of this community service is to provide knowledge to the community regarding personal hygiene to seaweed farmers in Pattitangngang Village, Mappakasunggu District, Takalar Regency. This counseling was conducted in Pattitangngang Neighborhood, Takalar Village, Mappakasunggu District, Takalar Regency which was attended by 29 people using lecture and question and answer methods. In addition, in this service a health check was also carried out, namely measuring blood sugar. Based on the results of this activity, it can be concluded descriptively that the output of this activity is the increase in community knowledge related to the importance of maintaining personal hygiene for seaweed farmers to avoid the risks of the work they do such as occupational diseases from the work. The community response to the implementation of this counseling was very enthusiastic. Seeing the activeness of some counseling participants who asked questions during the presentation of the material. In addition, the results of blood sugar checks found that there were 7 people who had prediabetes.